Frivolous Fear Over Feminized Medical Schools: Why Affirmative Action for Men is Not Justified - Matulewicz, Kaitlyn (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
In Canadian medical schools female students are outnumbering their male classmates. In response, the following question has been raised: should affirmative action for male applicants to Canadian medical schools be introduced? After investigating the gender composition of Canadian physicians across specialties, the experiences of women in medical schools, and the principles underlying affirmative action - as recognized by the Supreme Court of Canada - this article concludes that affirmative action for males applying to medical schools should not be introduced. A policy of affirmative action for male medical school applicants would give the illusion that sex equality within the field of medicine has been achieved. The greater representation of female students in Canadian medical schools should be celebrated as a chance to mitigate institutional barriers still faced by female physicians and professors within the medical field, rather than being approached as a concern. Dans les facultes de mkdecine canadiennes, les ktudiantes surpassent en nombre leurs camarades de classe masculins. La question suivante s’est donc posee : devraiton introduire l’action positive en faveur des candidats masculins? Cet article conclut, aprits avoir examine la composition par genre des mkdecins canadiens dans toutes les spkcialitCs, les experiences des femmes dans les Ccoles de mkdecineet les principes sous-jacents ii l’action positive (tels quTadoptCsp ar la Cour suprEme du Canada), que l’action positive en faveur du genre masculin ne devrait pas Etre introduite. Une politique d’action positive en faveur des candidats masculins aux 6coles de mCdecine donnerait l’illusion que llCgalitC des sexes dans le domaine de la mkdecine a CtC rkaliske. On devrait cClCbrer cette reprksentation plus importante des Ctudiantes dans les Ccoles de mkdecine canadiennes comme une chance dlattCnuer les barriilres institutionnelles auxquelles se heurtent les femmes mCdecins et professeurs du domaine m6dical au lieu de s’en inquiCter.